Optimization of drying and brewing conditions of cascara for kombucha production based on sensory characteristics - Gunawan, Muhammad Iqbal Fanani; Arwani, Afif; Faradiani, Alifa Rahma; Reyhan, Akmal; Duhita, Nada Syahda Ratna (Journal of Tropical AgriFood, 2026)
Indonesia is among the largest global coffee producers, with an output of 786.19 thousand tons in 2021, largely contributed by smallholder coffee plantations. Coffee fruit is composed of approximately 40% beans and 45% cascara, the latter of which is often discarded and underutilized despite its high polyphenol content. Improper disposal of cascara may cause environmental problems because of its acidity and antinutritional compounds. Cascara represents a promising raw material for functional beverages, such as kombucha, to increase its antioxidant potential. This study focused on developing cascara kombucha from coffee harvested in Magelang, Central Java, a region with distinct geographical characteristics that influence coffee quality. The cascara was dried at different temperatures (35, 40, and 45 °C for 24 h), brewed for 5 and 10 min, and subsequently fermented with a 10% (w/v) kombucha SCOBY for 8 d before pasteurization and storage. Sensory evaluation was performed by trained panelists using Quantitative Descriptive Analysis, followed by a hedonic acceptance test with 26 untrained panelists. The results demonstrated that drying at 45 °C combined with 5 min brewing yielded the highest hedonic score (4.88), while drying at 35 °C with 5 min brewing provided a comparable result (4.73) without significant difference. A longer brewing time (10 min) increased the turbidity. Optimization using DX13 analysis indicated that drying at 35 °C for 24 h and brewing for 5 min achieved the highest desirability for more effective production. These findings suggest that cascara kombucha has potential as a novel functional beverage, although further optimization is required to maximize its antioxidant and phenolic retention.